The growth of policies, rules, and regulations: A review of the literature and research agenda - Markus Hinterleitner; Christoph Knill; Yves Steinebach (Regulation & Governance, 2023)
This article reviews the vibrant literature on policy growth in political science and adjacent disciplines, thus offering a conceptual framework for situating past and future research efforts and facilitating the engagement between them. The first part presents important concepts that capture policy growth or aspects of it (rule growth, policy layering, policy mixes, policy accumulation, policyscapes, the policy state) and dominant measurement approaches. The second part provides an overview of the main drivers of policy growth in advanced democracies, discussing the role of societal demands, political competition, institutional fragmentation, and bureaucratic processes. The third part outlines the multi-faceted and far-reaching consequences of policy growth for policy, politics, and the polity. While policy growth is often portrayed as the price to pay for upholding the democratic capitalist order in constantly modernizing and diversifying societies, the existing research also points to the negative consequences emanating from increased state activity. Policy growth not only threatens to overburden bureaucracies and thereby undermine policy effectiveness; it may also transform the institutional structure of the democratic state and make its politics more complicated and conflictual.
Keywords: 330; bureaucracy; democracy; policy growth; policy state; regulatory growth; rule growth